2021
DOI: 10.3390/polym13193256
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: An Overview of Its Properties and Applications

Abstract: Chitosan has garnered much interest due to its properties and possible applications. Every year the number of publications and patents based on this polymer increase. Chitosan exhibits poor solubility in neutral and basic media, limiting its use in such conditions. Another serious obstacle is directly related to its natural origin. Chitosan is not a single polymer with a defined structure but a family of molecules with differences in their composition, size, and monomer distribution. These properties have a fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
356
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 592 publications
(361 citation statements)
references
References 206 publications
1
356
1
3
Order By: Relevance
“…Chitosan finds applications in pharmaceutics, biomedicine, packaging, wastewater treatment, cosmetics, food science, among others [ 6 , 57 , 58 ]. A comprehensive review of Acosta and coworkers was recently issued [ 59 ], and detailed information on the technological properties (such as solubility and viscosity), chemistry, and biological activities (such as antimicrobial, antioxidant, and anti-inflammatory activities) of chitosans are available. The authors additionally reviewed the use of chitosans in the green synthesis of metallic nanoparticles, as support for biocatalysts, and as versatile materials that can be exploited for the design of novel drug delivery systems.…”
Section: It All Started With Natural Polymersmentioning
confidence: 99%
“…Chitosan finds applications in pharmaceutics, biomedicine, packaging, wastewater treatment, cosmetics, food science, among others [ 6 , 57 , 58 ]. A comprehensive review of Acosta and coworkers was recently issued [ 59 ], and detailed information on the technological properties (such as solubility and viscosity), chemistry, and biological activities (such as antimicrobial, antioxidant, and anti-inflammatory activities) of chitosans are available. The authors additionally reviewed the use of chitosans in the green synthesis of metallic nanoparticles, as support for biocatalysts, and as versatile materials that can be exploited for the design of novel drug delivery systems.…”
Section: It All Started With Natural Polymersmentioning
confidence: 99%
“…It can be isolated and fabricated from bio-resources, including the exoskeletons of crustaceans, insects, mollusks, and fungi [15,16]. It attracts extensive attention in the biomedical field owing to its remarkable biological functions [17], and recently, the exploration of chitosan applications in food has expanded significantly [18]. Previously, we found that chitosan is capable of promoting the saltiness perception in food systems by incorporating the sodium chloride into microparticles to elevate the release of sodium ions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A good example of emerging bio-based technology is chitosan production. This material has gained a lot of attention mainly due to its properties and applications as a mucoadhesive, anti-inflammatory, antioxidant, and antifungal, among others [ 20 ]. Yu et al [ 21 ] described chitosan as a low-cost polymer with multiple physicochemical and biological properties for many applications in pharma, food, crop production, or biomedicine.…”
Section: Introductionmentioning
confidence: 99%